SYNTHETIC FLUID INCLUSIONS XIV: COEXISTING SILICATE MELT AND AQUEOUS FLUID INCLUSIONS IN THE HAPLOGRANITE-H2O-NACL-KCL SYSTEM - Student J.J.; Bodnar R.J. (My University, 1999)
Coeval silicate melt and aqueous synthetic fluid inclusions were formed at 800 degrees C and 2000 bars in the quartz-saturated haplo-granite-H2O-NaCl-KCl system. The equilibrium assemblage consisted of Ab(19.2)Or(31.1)Qtz(49.1) melt, quartz, and an aqueous solution with a composition of 7.4 wt % NaCl + 5.9 wt % KCl. The melt contained 0.18 wt % Cl- and similar to 5.5 wt % H2O. The calculated partition coefficient of chloride between the melt and aqueous fluid (D-Cl(m/aq) = C-Cl(m)/C-Cl(aq)) is 0.021. The calculated distribution coefficient of Na and K between the melt and the aqueous phase D-Na/K(m/aq) = (C-Na(m)/C-K(m))/(C-Na(aq)/C-K(aq))) is 0.40. Homogenization temperatures of synthetic silicate melt inclusions obtained by heating in 10.0 degrees C/day increments in a tube furnace agreed with known formation temperatures, with no size dependence. When measured in a high-temperature healing stage, a heating rate of 1 degrees C/min produced homogenization temperatures that were about 10 degrees C lower, than those obtained from the same inclusions using a heating rate of 3 degrees C/min, although both heating rates Produced homogenization temperatures above the formation temperature. A positive correlation between inclusion size and T-h was observed for both heating rates. Results confirm that microthermometric data from coeval silicate melt and aqueous fluid inclusions can be used to accurately predict P-T formation conditions if data from the smallest melt inclusions are used, or if the melt inclusions are homogenized using a slow heating rate (<1 degrees C/min).